2007
DOI: 10.1021/jp074586o
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Dynamics Study of Intrasurface Hydrogen-Bonding Effects in Gas−Surface Energy Exchange and Accommodation

Abstract: Classical chemical dynamics simulations were performed to compare the efficiency of energy transfer in collisions of Ar with 300 K CH3- and OH-terminated alkyl thiol self-assembled monolayer surfaces (i.e., H-SAM and HO-SAM) and compare with previous experiments (Anal. Chim. Acta 2003, 496, 249). The experiments show that energy is transferred less efficiently to the HO-SAM. The H-SAM has a periodic, ordered surface structure, whereas the surface of the HO-SAM has a disordered, “glassy” structure as a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 54 publications
8
75
0
Order By: Relevance
“…2(a)). Especially in the OH-terminated SAM system, it was reported that terminal OH groups form a network structure in the surface plane due to hydrogen bonding [29], which is likely to be susceptible to potential models. 2(b)).…”
Section: Heat Transfer Characteristics At the Interfacementioning
confidence: 99%
“…2(a)). Especially in the OH-terminated SAM system, it was reported that terminal OH groups form a network structure in the surface plane due to hydrogen bonding [29], which is likely to be susceptible to potential models. 2(b)).…”
Section: Heat Transfer Characteristics At the Interfacementioning
confidence: 99%
“…10,11 For low collision energies the ion may adsorb on the surface intact, with or without charge retention, a process referred to as SL. [28][29][30][31][32][33][34][35][36][37][38][39][40][41]45 Energy transfer probabilities to the surface and projectile may be determined, [28][29][30][31][32][33][34][35][36][37][38][39][40][41]45 as well as features of the collision such as the importance of surface penetration 29,[33][34][35][36]41,46,47 or physisorption. 13 SL and RL have numerous uses, [12][13][14][15][23][24][25]42 including preparation of protein or peptide a...…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Fairbrother and co-workers have also examined the destruction of alkyl, fluorinated, and X-raymodified SAMs by a thermalized mixture of atomic and molecular oxygen (O( The first such experiment was carried out by Naaman and coworkers 10 using molecular beams of He, Ar, NO, and O 2 from alkyl and fluorinated SAMs and time-of-flight mass spectrometry (TOF-MS) to detect the scattered species. Subsequent work by Siebener and co-workers [11][12][13][14][15] and, most comprehensively, by Morris and co-workers [16][17][18][19][20][21][22][23][24][25][26] has investigated the effects of varying the identity of the impinging gas, impact angle, final angle, initial energy, monolayer temperature, SAM terminal group, alkyl chain length, and metal substrate (hence, surface density). This has led to a wealth of information on factors affecting energy transfer at the gas-SAM interface.…”
Section: Introductionmentioning
confidence: 99%